Identifying priorities for post‐fire restoration in California chaparral shrublands. Issue 3 (27th September 2021) - Underwood, Emma C.; Hollander, Allan D.; Molinari, Nicole A.; Larios, Loralee; Safford, Hugh D.
Abstract : When wildfires occur at sufficiently low frequencies, chaparral shrubland regenerates without the need for active restoration. However, shrubland with high fire frequency, particularly in conjunction with other stressors, can require active restoration. Here we present a Post‐fire Restoration Prioritization (PReP) tool for chaparral shrublands which identifies priorities for post‐fire restoration based on the regeneration potential of shrubs and accounts for fire history, drought tolerance, and competition from annual grasses. We demonstrate the tool on the Copper (2002) and Powerhouse (2013) fires on the Angeles National Forest and determine that 9% (665 ha) and 14% (1, 532 ha) of the fire areas, respectively, have low regeneration capacity, and therefore represent priority areas for restoration. For more recent fires (≤2 years ago), an additional component of the tool integrates erosion risk data to identify locations where active restoration may enhance hillside stabilization. To ground‐truth tool outputs for the Powerhouse Fire, we sampled 57 plots to assess if recovery was indeed impeded in low versus high regeneration capacity classes. Low regeneration plots exhibited significantly higher grass and herbaceous cover, with high abundance of non‐native species. Furthermore, resprouting shrub species contributed proportionally more cover than obligate seeders in low regeneration plots, with fewer individuals regenerating from seed compared to resprouting. These findings underscore the potential of the PReP tool to provide credible spatial guidance for shrubland management, both in California and potentially in other Mediterranean‐type climate regions, as to where active restoration is most likely to ensure long‐term sustainability of chaparral and associated ecosystem services.